PENGARUH PENJUALAN ADAPTIVE, KAPABILITAS RELASI, KETERAMPILAN MENJUAL TERHADAP KINERJA TENAGA PENJUALAN - Putri Ardela, Febiana; Augustine Graciafernandy, Maria (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2024)
This research aims to analyze the influence of adaptive selling, relationship capabilities, and selling skills on sales force performance in a business context. The quantitative method was used by distributing questionnaires to 100 respondents who were salespeople. Adaptive selling is measured by the level of sales force's ability to adjust sales strategies according to customer needs. Relationship capability is assessed based on the ability to build and maintain strong relationships with customers. Meanwhile, selling skills are measured through communication skills, building good relationships with customers. In this research, data collection was carried out using a Google Form questionnaire and data analysis using SPSS version 26 which included descriptive analysis, validity test, reliability test, classical assumption test, multiple regression analysis, significance test using the t test, f test, and R2 test. The results of this research show that adaptive selling (X1), relationship capability (X2), and selling skills (X3) influence sales force performance (Y).